Synthesis, characterization and application of ion imprinted poly(vinylimidazole) for zinc ion extraction/preconcentration with faas determination - Santos,Queila O. dos (2014)
In this paper, we describe the synthesis of an ion imprinted polymer (IIP) by homogeneous polymerization and its use in solid-phase to extract and preconcentrate zinc ions. Under optimal conditions (pH 5.0, preconcentration flow rate of 12.0 mL min-1, and eluted with 1.0 mol L-1 HNO3) this procedure allows the determination of zinc with an enrichment factor of 10.2, and with limits of detection and quantification of 1.5 and 5.0 µg L-1, respectively. The accuracy of our results was confirmed by analysis of tap water and certified reference materials: NIST 1570a (Spinach leaves) and NIST 1515 (Apple leaves).